2006
DOI: 10.2133/dmpk.21.54
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Efficacy of Maeda’s Nomogram for Vancomycin Dosage Adjustment in Adult Japanese MRSA Pneumonia Patients

Abstract: The clinical efficacy of Maeda's nomogram for vancomycin dosage adjustment was evaluated by comparison with a standard dosage regimen (package insert information: vancomycin dose reduced in elderly patients and patients with renal dysfunction, with Moellering's nomogram used for renal-dysfunction patients) in adult Japanese MRSA pneumonia patients. Using Maeda's nomogram, the vancomycin dose is fixed at 1,000 mg while the dosing interval is varied in accordance with individual creatinine clearance. Using a sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Several studies [43][44][45][46] report VCM dose nomograms, based on pre-defined TTCRs and patient characteristics. The dose is directly selected from the nomogram, and patients tend to have VCM trough concentrations within the target range, as compared to traditional methods [45,52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies [43][44][45][46] report VCM dose nomograms, based on pre-defined TTCRs and patient characteristics. The dose is directly selected from the nomogram, and patients tend to have VCM trough concentrations within the target range, as compared to traditional methods [45,52].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, most reports only contain one VCM nomogram, which corresponds to one TTCR using only one PK model. However, there are many recommended TTCRs that vary between reports [12,[44][45][46]53]. One nomogram from one PK model could not be applied to all TTCRs, which may be inconvenient, since the TTCR may vary between patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the period considered by our study, the protocol set a weight-based loading dose of 1000 mg for patients with a body weight <65 Kg, and 1500 mg for patients with a body weight >65 Kg [ 5 ], diluted in a 100 ml of saline solution and administered over 60 minutes when the loading dose was 1000 mg; and over 90 min when the loading dose was 1500 mg. The loading dose was followed by the infusion of a dose of vancomycin calculated according to the CrCl [ 17 ]: specifically, 2000 mg/day if creatinine clearance was >50 ml/min/1,73 m 2 , 1500 mg/day if creatinine clearance was between 20–50 ml/min/1,73 m 2 , 1000 mg/day if creatinine clearance was between 10–20 ml/min/1,73 m 2 and 500 mg/day if creatinine clearance was < 10 ml/min/1,73 m 2 . Consecutive infusion rate was adjusted according to VSC: the daily dose was increased by 500 mg when VSC was <15 mg/L, left unchanged when VSC was between 15–25 mg/L, and was decreased by 500 mg when VSC was >25 mg/L and the infusion was interrupted for 6 hours when VSC exceeded 30 mg/L [ 5 , 7 ] (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, nomograms have been analyzed with the intention to improve dosing patterns, but they failed to help in achieving sufficient vancomycin serum levels [6]. Similarly, using dosing recommendations provided by the current vancomycin product information has been demonstrated to be even worse for obtaining target serum levels [7]. Consequently, TDM is recommended to guide vancomycin therapy [3], and data from a recent clinical trial showed that repeated measurements increase the safety of target serum levels in a subset of medical ICU patients [8].…”
Section: Introductionmentioning
confidence: 99%